Synthesis and Characterization of Nerv Sulfadiazine and SulfapyridineDerivatives - Kahtan Abddulla, Iebtehal (Tikrit Journal of Pharmaceutical Sciences, 2023)
A series of 4-Hydroxybenzosulfadiazine (1, ia, lb, 3) and sulfapyridine (2,2a,2b,4) derivatives, were prepared by condensation of appropriate sulfadiazine, sulfapy'ridine with 4- hydroxybenzoic acid in the presence of molecular sieves followed by 2-amino methylation on hydroxy group.